Bringing the Malaysian curriculum into the 21st century - Abdullah, Hazlina; Mohd. Asraf, Ratnawati (American Scientific Publishers, 2017)
This paper discusses the types of knowledge, skills and abilities that young generations of Malaysians should possess throughout their years of schooling and whether the current curriculum is adequate in enabling the students to face the challenges of the 21st century. Grounded in the Malaysian Educational Philosophy, Malaysian Educational Act, and its national Vision 2020, and taking into consideration the needs of the students and the nation in meeting these challenges, this paper proposed a curriculum for young Malaysians based on three key questions proposed by the Qualifications and Curriculum Authority; a curriculum that promotes learning from multi-disciplinary studies and that encourages physical, emotional, spiritual, personal and social competencies. In designing this curriculum, the authors stress on the importance of catering to the needs, interests and aspirations of our multi-racial society and the importance of incorporating spiritual and moral values that would help young Malaysians to face these challenges. This paper concludes by proposing a framework adapted from the QCA that could be used as a starting point for the discussions on the 21st century curriculum.